(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the clinical and paraclinical characteristics of encephalitis-meningitis in children at the Pediatric Center of Bach Mai Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 120 pediatric patients with encephalitis-meningitis at the Pediatric Center of Bach Mai Hospital from August 2024 to August 2025. Results: Clinical characteristics: headache/crying accounted for 97.5%; fever 86.7%; vomiting 85%; stiff neck 63.3%; Kernig’s sign 28.3%; seizures 2.5%. Paraclinical characteristics: the percentage of patients with WBC > 10G/l was 68.3%. In meningitis, the percentage of cerebrospinal fluid leukocytes >250 (cells/mm3) was 37.4%, higher than in encephalitis (7.7%), with a higher incidence of meningitis. Glucose levels between 2.5 and 4 mmol/l accounted for 90%; chloride levels ≥ 120 mmol/l accounted for 82.2%. The cause of death was unknown in 33.3% of patients, with all identified causes being viral. Enterovirus was the most common cause at 60%. Of the 35 patients who underwent cranial MRI, 10 (28.6%) showed abnormalities and 25 (71.4%) showed no abnormalities. CT scans of all 15 patients showed no abnormalities.